A participação e o padrão decisório no conselho municipal de educação de Araras no ano de 2019 - Marangoni, Pedro Cabrini [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
In the 21st century, the thought of participatory democracy gained interesting contours: in Brazil, the efforts of social mobilization and the new constitution allowed the emergence of participatory institutions, which expanded citizen participation in decision-making spaces for public policies. Social participation has expanded into several areas of public policy, including education: the constitution that proclaimed education as a fundamental subjective right, also instituted a federative model in the execution of education policies and strengthened a complementary participatory model. Such participatory model is manifested, at the local level, through the municipal councils of education, a participatory design characterized by the sharing of power between public administration agents and civil society actors. The municipal councils of education have two main functions: influencing the local education system and contributing to the construction of the state and federal education system; through its normative, deliberative and consultative attributions. Once the relevance of municipal education councils is understood as a local participatory forum, local practice must be analyzed in order to verify whether participation in municipal education councils fulfills their dual function. Therefore, the aim of this study is to identify the intersection between municipal public policy councils and the education system in Brazil; and verify how participation can influence public education policies in the Municipality of Araras and assess the decision-making standard of the Municipal Council of Education of Araras. This is a descriptive and exploratory study; the technique of bibliographic research in published materials is adopted as a method of procedure (articles, legislation, doctrines, jurisprudence, contents available on electronic sites, etc.); and, as a method of approach, the hypothetical-inductive approach, in order to verify hypotheses based on a specific case, through the interpretation of data collected in the literature review and in public documents; and, thus, foreshadowing the reality of the Municipal Council of Education of Araras, aiming to deepen the debate on the expansion of social participation in municipal councils.

No Século XXI, o pensamento da democracia participativa ganhou contornos interessantes: no Brasil, os esforços da mobilização social e da nova constituição permitiram o surgimento das instituições participativas, o que ampliou a participação cidadã nos espaços decisórios de políticas públicas. A participação social expandiu-se por diversas áreas das políticas públicas, dentre elas a educação: a constituição que proclamou a educação como um direito fundamental subjetivo, instituiu também um modelo federativo na execução das políticas de ensino e fortaleceu um modelo complementar participativo. Tal modelo participativo se manifesta, a nível local, por meio dos conselhos municipais de educação, um desenho participativo caracterizado pela partilha do poder entre agentes da administração pública e atores da sociedade civil. Os conselhos municipais de educação concentram duas principais funções: influenciar no sistema de ensino local e contribuir com a construção do sistema de ensino estadual e federal; por meio das suas atribuições normativa, deliberativa e consultiva. Entendida a relevância dos conselhos municipais de educação, como fórum participativo local, a prática local deve ser analisada de modo a se verificar se a participação nos conselhos municipais de educação satisfaz a dupla função desses. Diante disso, o objetivo do presente estudo é identificar a intersecção entre os conselhos municipais de políticas públicas e o sistema de ensino no Brasil; e verificar como a participação pode influenciar nas políticas públicas de educação do Município de Araras e aferir o padrão decisório do Conselho Municipal de Educação de Araras. Trata-se de um estudo de natureza descritiva e exploratória; adota-se, como método de procedimento, a técnica de pesquisa bibliográfica em materiais publicados (artigos, legislação, doutrinas, jurisprudência, conteúdos disponibilizados em sítios eletrônicos etc.); e, como método de abordagem, o hipotético-indutivo, a fim de se verificar hipóteses a partir de um caso concreto, por meio de interpretação de dados levantados em na revisão bibliográfica e em documentos públicos; e, assim, prenunciar a realidade do Conselho Municipal de Educação de Araras, visando aprofundar o debate sobre a ampliação da participação social nos conselhos municipais.
Participation and decision-making pattern in the Araras municipal education council in the year 2019
Keywords: Participatory democracy; Participatory institutions; Municipal councils; Participation; Decision pattern; Participação; Instituições participativas; Padrão decisório; Conselhos municipais; Democracia participativa